Kajian Antropologi Kristen Mengenai Peran Guru Menerapkan Strategi Pembelajaran Variatif untuk Mengembangkan Kemampuan Afektif Siswa [A Christian Anthropology Review on The Role of Teachers in Implementing the Variative Learning Strategy to Develop Students' Affective Ability] - Maria Kezia Gaghunting; Jessica Bermuli (Diligentia: Journal of Theology and Christian Education, 2022)
The application of learning strategies can help teachers to be able to improve students' affective abilities. However, it is not uncommon for a teacher to use an inappropriate learning strategy that makes learning unproductive. Learning strategies must be varied and aligned with students' needs so that their learning abilities can increase. The purpose of this paper is to examine the importance of Christian anthropological studies regarding the role of teachers in applying varied learning strategies to develop students' affective abilities. This paper is conducted using the literature review method. Teachers need to realize that students are human beings created by God, has fallen into sin, and in restoration stage. Therefore, teachers have to deliver the lessons that awaken students to God's forgiving love, redemption by Christ, and the renewal of the Holy Spirit. The Bible as the source of absolute truth must be the basis of every study. Additionally, by understanding the characteristics of students, teachers can apply learning strategies according to learning needs so that students' affective abilities can be developed. The teacher's role as manager will design learning activities so that it has a big influence on the development of students' affective abilities. Teachers are advised to need to master and even use various technologies to be developed innovatively to support learning in the classroom.